The impact of sex and knee injury history on jump-landing patterns in collegiate athletes: A clinical evaluation - Lam, K. C.; Valovich McLeod, T. C. (Clinical Journal of Sport Medicine, 2014)
Objective: To determine whether jump-landing patterns, as assessed by the Landing Error Scoring System (LESS), differ based on sex and knee injury history. Design: Cross-sectional. Setting: College. Participants: Two hundred fifteen intercollegiate athletes were grouped by sex (male = 116 and female = 99) and self-reported knee injury history (no = 148, mild = 31, and severe = 36). Interventions: Participants performed 3 trials of a standardized jump-landing task that were videotaped and later scored using the LESS. Main Outcome Measures: Overall, individual item, sagittal total error, and frontal total error scores of the LESS. Results: An interaction effect was reported for trunk flexion at initial ground contact. Main effects for sex indicated that males demonstrated more at-risk landing movement patterns on the sagittal plane (ie, limited trunk, knee and hip flexion at initial contact, and limited hip flexion throughout the landing), whereas females demonstrated more at-risk landing movement patterns on the frontal plane (ie, knee valgus at initial ground contact and maximum knee flexion, and more frontal plane movement throughout the landing). No main effects were reported for injury history. Conclusions: Jump-landing patterns seem to be impacted by sex but not knee injury history. Findings related to sex differences corroborate with previous laboratory-based investigations. Furthermore, findings support the clinical use of the LESS to screen for individuals who may be at risk for a lower extremity injury. Future studies should further investigate the clinical utility of the LESS, particularly its ability to predict lower extremity injuries.